“Left Neglected,” but Only in Far Space: Spatial Biases in Healthy Participants Revealed in a Visually Guided Grasping Task - de Bruin, Natalie; Bryant, Devon; Gonzalez, Claudia L. (Frontiers in Neurology, 2014)
Hemispatial neglect is a common outcome of stroke that is characterised by the inability to orient towards, and attend to stimuli in contralesional space. It is established that hemispatial neglect has a perceptual component, however, the presence and severity of motor impairments is controversial. Establishing the nature of space use and spatial biases during visually-guided actions amongst healthy individuals is critical to understanding the presence of visuomotor deficits in patients with neglect. Accordingly, three experiments were conducted to investigate the effect of object spatial location on patterns of grasping. Experiment 1 required right-handed participants to reach and grasp for blocks in order to construct 3D models. The blocks were scattered on a tabletop divided into equal size quadrants: left near, left far, right near, and right far. Identical sets of building blocks were available in each quadrant. Space use was dynamic, with participants initially grasping blocks from right near space and tending to ‘neglect’ left far space until the final stages of the task. Experiment 2 repeated the protocol with left-handed participants. Remarkably, left-handed participants displayed a similar pattern of space use to right-handed participants. In Experiment 3 eye movements were examined to investigate whether ‘neglect’ for grasping in left far reachable space had its origins in attentional biases. It was found that patterns of eye movements mirrored patterns of reach-to-grasp movements. We conclude that there are spatial biases during visually-guided grasping, specifically, a tendency to neglect left far reachable space, and that this ‘neglect’ is attentional in origin. The results raise the possibility that visuomotor impairments reported among patients with right hemisphere lesions when working in contralesional space may result in part from this inherent tendency to ‘neglect’ left far space irrespective of the presence of unilateral visuospatial neglect.